Development of soy‐based nanocomposite film: Modeling for barrier and mechanical properties and its application as cheese slice separator. Issue 6 (9th October 2021) - V., Ajesh Kumar; M., Pravitha; Srivastav, Prem Prakash; Mangaraj, Shukadev; R., Pandiselvam; Hasan, Muzaffar
Abstract: In the current study, soybean aqueous extract (SAE)‐based nanocomposite film was developed by incorporating cellulose nanofiber (CNF) at various concentrations (0–10%). Effect of nanoreinforcement on essential properties of the nanocomposite film such as barrier, mechanical, water affinity, and optical properties were evaluated. Homogeneous films with improved barrier and mechanical properties were observed until 6% CNF, beyond which considerable reduction in desirable properties was noticed due to nanoparticle's agglomeration effect. Furthermore, the prediction of the mechanical and barrier properties of nanocomposite film was performed with mathematical models such as modified Halpin–Tsai and modified Nielsen equations, respectively. The model‐fitting results reveal that the theoretically predicted values were in close agreement with the experimental values. Hence, these models were well suited for predicting respective properties. Model prediction also implies that the increase in the aspect ratio of fillers can considerably cause a reduction in water vapor permeability and improvement in mechanical properties. Suitability of developed film as cheese slice separator was evaluated: they had equivalent outcomes in terms of easiness in slice separation and wholeness of slices after separation compared to the commercial material. Abstract : Developed nanocomposite film from a less explored source, soybean aqueous extract, with tailored properties by cellulose nanofiber reinforcement. The modeling approach for better prediction of barrier and mechanical properties as a function of nanofiller concentration was also examined. Moreover, the suitability of the developed film as a cheese slice separator was successfully demonstrated.